Acute kidney injury, persistent kidney disease, and post-discharge morbidity and mortality in severe malaria in children: A prospective cohort study. (February 2022) - Namazzi, Ruth; Batte, Anthony; Opoka, Robert O.; Bangirana, Paul; Schwaderer, Andrew L.; Berrens, Zachary; Datta, Dibyadyuti; Goings, Michael; Ssenkusu, John M.; Goldstein, Stuart L.; John, Chandy C.; Conroy, Andrea L.
Summary: Background: Globally, 85% of acute kidney injury (AKI) cases occur in low-and-middle-income countries. There is limited information on persistent kidney disease (acute kidney disease [AKD]) following severe malaria-associated AKI. Methods: Between March 28, 2014, and April 18, 2017, 598 children with severe malaria and 118 community children were enrolled in a two-site prospective cohort study in Uganda and followed up for 12 months. The Kidney Disease: Improving Global Outcomes (KDIGO) criteria were used to define AKI (primary exposure) and AKD at 1-month follow-up (primary outcome). Plasma neutrophil gelatinase-associated lipocalin (NGAL) was assessed as a structural biomarker of AKI. Findings: The prevalence of AKI was 45·3% with 21·5% of children having unresolved AKI at 24 h. AKI was more common in Eastern Uganda. In-hospital mortality increased across AKI stages from 1·8% in children without AKI to 26·5% with Stage 3 AKI ( p  < 0·0001). Children with a high-risk plasma NGAL test were more likely to have unresolved AKI (OR, 7·00 95% CI 4·16 to 11·76) and die in hospital (OR, 6·02 95% CI 2·83 to 12·81). AKD prevalence was 15·6% at 1-month follow-up with most AKD occurring in Eastern Uganda. Risk factors for AKD included severe/unresolved AKI, blackwater fever, and a high-risk NGAL test (adjusted p  < 0·05). Paracetamol use during hospitalization was associated with reduced AKD ( p  < 0·0001). Survivors with AKD post-AKI had higher post-discharge mortality (17·5%) compared with children without AKD (3·7%). Interpretation: Children with severe malaria-associated AKI are at risk of AKD and post-discharge mortality. Funding: This work was supported by the National Institutes of Health National Institute of Neurological Disorders and Stroke (R01NS055349 to CCJ) and the Fogarty International Center (D43 TW010928 to CCJ), and a Ralph W. and Grace M. Showalter Young Investigator Award to ALC.